2004
DOI: 10.1161/01.cir.0000138930.12773.41
|View full text |Cite
|
Sign up to set email alerts
|

Severe Aortic Stenosis and Myocardial Function

Abstract: Background— The aim of this study was to assess the myocardial reflectivity pattern in severe aortic valve stenosis through the use of integrated backscatter (IBS) analysis. Patients with aortic stenosis (AS) were carefully selected in the Department of Cardiology. Methods and Results— Thirty-five subjects (AS: valve orifice ≤1 cm 2 ; 12 female; mean age, 71.8±6.2 years) and 25 healthy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…In experimental studies, IBS absolute values have been shown to be reliable indices of LV fibrosis. In addition, they have been shown to reflect myocardial collagen content as assessed by endomyocardial biopsy in humans (15,16,18). It has been demonstrated that even mild reductions in renal function are associated with a greater prevalence of LVH (27,28); the increase in IBS reflectivity that was observed in our study also indicates an early increase in LV collagen deposition, beginning well before the development of ESRD.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In experimental studies, IBS absolute values have been shown to be reliable indices of LV fibrosis. In addition, they have been shown to reflect myocardial collagen content as assessed by endomyocardial biopsy in humans (15,16,18). It has been demonstrated that even mild reductions in renal function are associated with a greater prevalence of LVH (27,28); the increase in IBS reflectivity that was observed in our study also indicates an early increase in LV collagen deposition, beginning well before the development of ESRD.…”
Section: Discussionsupporting
confidence: 63%
“…Already in 1985 Wickline et al (29) observed in open-chest dogs that a reduced IBS CV may be paralleled by a reduction in LV contractile performance. At the same time, IBS CV was found to be significantly and inversely related to the percent fibrosis area as assessed by endomyocardial biopsy in patients with dilated cardiomyopathy (17) and to the myocardium/fibrosis ratio in patients with aortic stenosis (18). Furthermore, in patients with EH, a decreased CV of backscatter signal is associated with an increase in serum procollagen type I C-peptide, a specific circulating marker of cardiac collagen content (30).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, these indexes sometimes correlate poorly with patient symptoms and depend on stroke volume. 7,8 Furthermore, ejection fraction may be related mainly to global radial function, which is reduced only in end-stage disease. 9 Importantly, fibrotic changes induced by aortic stenosis start subendocardially 1 and affect mainly longitudinal function, which is not well represented by ejection fraction.…”
Section: Clinical Perspective On P 584mentioning
confidence: 99%
“…10, 11 Although European and US guidelines advise using hemodynamic parameters that represent the severity and parameters of global LV systolic function at rest, 12,13 these indices sometimes correlate poorly with patient symptoms. 14, 15 Recent investigations have confirmed that myocardial fibrosis is an important morphological substrate of LVH and is not reversible after AVR. 16 Together, these findings indicate the need to comprehensively evaluate diastolic function in AS patients to characterize the hemodynamic derangements that take place in AS.…”
mentioning
confidence: 99%